The Evolution of Amphibian Photoreception - Mohun, Samantha Mila; Davies, Wayne Iwan Lee (Frontiers in Ecology and Evolution, 2019)
There have been a growing number of studies into the visual evolution of vertebrates. However, there remain few detailed integrative studies on the visual system of amphibians using morphological, molecular and physiological methods outside of a few model species. There are many examples of amphibian species that are closely related phylogenetically, but occupy vastly different ecological niches and so provide a substantial resource for the study of adaptive evolution. This review will examine the published literature on the three living orders of amphibians, the Anurans, Caudata, and Gymnophiona.